IMPLEMENTASI LINGKUNGAN SOSIAL TERHADAP PEMBENTUKAN PERILAKU EMPATI REMAJA - Shinta Fitriani Kosasih; Muhammad Fadlan Choiri; Husna Nafilah; Muhammad Fahrul Rozi Pasya; Dika Sahputra (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2023)
The social environment is the second aspect besides the family that gives the most influence in shaping the attitude and psychological maturity of adolescents, empathetic behavior is the main concern in this compilation. Descriptive qualitative, the results of the research can be recognized if the social environment plays a major role in creating empathetic behavior in adolescents. The method used is qualitatively adopted in order to take advantage of the objectivity offered by research to evaluate social phenomena in the environment by taking a sample of 5 people who come from different walks of life and levels of education. In addition, the authors also take samples of having and not having children. teenager. The results of the study show that adolescents are often more concerned with the opinion of the social environment about their personality than the opinion of their parents and family. Teenagers tend to put aside empathy because, for teenagers, helping other people they don't know and feel there is no advantage for them to do so, teenagers will think many times before deciding whether to take part or not, and sometimes teenagers also let other people who have difficulties with the attitude of "pretending not to see" and if someone reminds them to help, it is not uncommon for teenagers to say "someone will help later".